Mulheres em dois tempos: a representação feminina entre o trovadorismo português e a sofrência pop de Duda Beat - Ferraz, Maria Eduarda Campos de Sá (2022)
This research aims to study the troubadour poetry and its possible reflections on contemporary brazilian music, represented in the work by the musical genre of Sofrência Pop and the artist Duda Beat. In addition to that, it proposes the formation of a new genre in the current productions, the “Response”. Divided in order to present the society and the time in which the productions appears, aiming a better understanding of both, the research brings the Portuguese troubadourism from the contextualization of the Middle Ages, period of its emergence, and the same happens with the Sofrência Pop, within the contemporary world. The discussion between the times also extends to the representation of one era in the other, through audiovisual production, literature and other forms of art. As a scientific methodology, we use the Content Analyses, proposed by Laurence Bardin (1977), and the analysis develops around Duda Beat’s debut album, “Sinto Muito”, released in 2018. By categorizing the common features in the troubadour songs, studying and observing the stories and ways used by the singer, while describing her love and pain, it is possible to identinfy the reproduction of the characteristic elements of the past in the present, and to perceive the space of response being built by contemporary women in Brazilian Sofrência Pop.